La revolución de Túpac Amaru - Flores Galindo, Alberto, 1949-1990 (SAGSA, 1978)
No presenta resumen.
1 fotografía : byn
Keywords: Tupac-Amaru, José Gabriel, 1742-1781; Revoluciones--Perú--Historia; https://purl.org/pe-repo/ocde/ford#6.00.00